PENDAPATAN DAN KELAYAKAN USAHATANI PADI DI DESA LETBAUN KECAMATAN SEMAU KABUPATEN KUPANG - Kollan, Ermi I; Nampa, I Wayan; Chamdra, Santhy (Buletin Ilmiah Impas, 2023)
This research was carried out in Letbaun Village, Semau District, Kupang Regency. In August-September 2022. The research aims to determine (1) the size of farmers' income and (2) the feasibility of rice farming in Letbaun Village, Semau District, Kupang Regency. Data was collected by interviewing 60 farmers (Census). Data analysis was carried out in a quantitative descriptive manner. The results showed that the average income of the respondent,s pet rice farming in Letbaun village, Semau district was of IDR .6,488 148.75, while the income per hectare received by respondent farmers was of IDR.10.191.439. Rice farming in Letbaun Village, Semau District, Kupang Regency worth cultivating with and R/C Ratio of 3.64. Rice production is greater than BEP production (76697 kg > 21,080kg) and the rice price of IDR 7,000/kg is above the BEP price of IDR. 1,924/kg.And the results of the research, rice farming in Letbaun Village, Semau District, Kupang Regency, is feasible to work on.